Pengaruh Penerapan Metode Al-Muyasar Terhadap Kemampuan Membaca Al-Qur’an Pada Siswa Kelas Vii Di Mts Ar-Rifa’i Bogor - Nahdiatun Niswah; Muhyani Muhyani; Nurman Hakim (Universitas Pahlawan Tuanku Tambusai, 2024)
The Al-Muyassar method can enable students at MTs Ar-Rifa'i to be able to read the Al-Qur'an fluently and correctly according to recitation. The difference between the al-Muyasar Al-Qur'an reading method and other Al-Qur'an reading methods is that the al-Muyasar learning method is easy, fun and touching. So from this the researcher formulated the problem, namely